KOMPONEN PARIWISATA DAN DAYA DUKUNG KAWASAN DI PULAU LIWUNGAN - Febriana Febriana; Fahrurozy Darmawan; Singgih Tri Wibowo (JURNAL KEPARIWISATAAN, 2022)
Liwungan Island is only mainstays of marine tourism in the Tanjung Lesung Beach tourist area. This area has been equipped with adequate infrastructure and supporting facilities, such as telecommunications networks with international and local telecommunications service facilities, electricity networks and clean water facilities. Based on the findings of the condition of tourism component, Liwungan Island has its own charm but is not supported by adequate access and facilities. In addition to the difficulty of getting public transportation, the condition of the Tanjung Jaya Village port which is the only access for tourists to Liwungan Island is still a concern, in the end tourism on Liwungan Island has stagnated. Mixed methods or hybrid methods are used in this study. Based on the results of the Liwungan Island tourism experience survey, it was found that tourists' expectations of the experiences they got while visiting Liwungan Island were not met, while the Tanjung Lesung area had been designated as one of the 10 Priority Tourism Destinations in Indonesia. With the spread of attractions in the area, one of which is Liwungan Island, research on the tourism component, tourism carrying capacity and tourist experience of the area becomes a very important thing to do.